Charakterystyka współczesnego terroryzmu - Antonów, Radosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Contemporary terrorism is one of the most serious threats to the world today. Since the second half of the 20th century it has evolved, adapting its aspirations, needs and capabilities to the scientific, technological and informational development of the world today as well as the geopolitical situation and specifi city. Thus contemporary terrorism is a dynamic process and rarely, or increasingly rarely, a state that remains unchanged. The essence of terrorism today lies the fact that it is commonly regarded as a threat not only to national security security within one state but, above all, to international security in view of the globalisation of terrorism. Contemporary terrorism has four basic features. First of all, it is inspired by religion. Secondly, the perpetrators do not reveal their identity, remaining in hiding and preparing new attacks. Thirdly, the actions of terrorists are much more deadly than ever before and, finally, terrorism is global. In addition, terrorism today is linked to actions focused on producing victims on a mass scale. This may suggest a development of genocidal terrorism which will be particularly evident in any future ethnic conflicts. A permanent characteristic feature of terrorism, including contemporary terrorism, is its objectives: to attract attention, generate publicity, justify its actions, win social consent and, finally, seize power. Preventing and combating contemporary terrorism requires not only the work of institution and agencies established for that purpose, but also responsible functioning of every individual in society. Thus creating security today requires collaboration of all people.
Keywords: terroryzm; bezpieczeństwo narodowe; bezpieczeństwo międzynarodowe; wojna; zagrożenie bezpieczeństwa